MAKING LEARNING MEDIA FOR GREENBOX EFFECT SIMULATOR TO IMPROVE UNDERSTANDING OF THE CONCEPT OF THE GREENHOUSE EFFECT - Noer Sarifah Ainy; Nestiyanto Hadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The earth is experiencing global warming due to an increase in air temperature (greenhouse effect). This is due to the large number of greenhouse gases produced by human activities. In addition, it is also due to the reduced number of plants that absorb greenhouse gases, especially carbon dioxide. This condition causes the study of the greenhouse effect to become an object studied by students at school. Understanding the greenhouse effect is somewhat difficult if only understood in theory. Increasing understanding can be done by making practicum learning media. This study aims to create learning media for the Greenbox Effect Simulator to help understand the concept of the greenhouse effect. The research was conducted using control variables and independent variables (use of plants and without plants). The plants used are Caisim, Sri Gading and Anggrek. The presence of carbon dioxide (CO2) greenhouse gases can be detected by three things, namely changes in the color of the CO2 indicator, changes in temperature, and visibility of the box. The color of the CO2 indicator shows green and green yellow for Box B (with plants) which means the concentration of CO2 in normal conditions. Whereas Box C (without plants) gives a yellow color, which means that the concentration of CO2 is at high conditions. The presence of carbon dioxide gas from combustion will increase the temperature by 1.4 - 1.9 oC in Box C (without plants) and 0.7 - 1.5 oC in Box B (use of plants). The visibility of Box B shows a higher brightness level than Box C. The best plants that can absorb CO2 concentrations are orchids. The ability of orchids to absorb CO2 is assisted by their roots which also function to carry out photosynthesis. The existence of plants functions to absorb CO2 quite well when viewed from changes in temperature, color indicators and visibility.